PENGARUH KONSENTRASI ZPT ALAMI DAN BEBERAPA VARIETAS TERHADAP PERTUMBUMHAN STEK TANAMAN TIN DI LAHAN SALIN: KONSENTRASI ZPT ALAMI DAN BEBERAPA VARIETAS TERHADAP PERTUMBUMHAN STEK TANAMAN TIN DI LAHAN SALIN - Ari Handriatni; Nafila Mariska (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study aims to determine the effect of initial immersion temperature and type of planting media on germination of Silk Tree seeds. The study was conducted in East Rejosari, Tersono, Batang Regency from December 2019 to February 2020 using a Randomized Block Design (RBD) consisting of 2 factorials which were repeated 3 times. The first factor is initial immersion temperature is room temperature, 30˚C, 60˚C, and 90˚C, the second factors is type of planting media consisting of 3 levels namely soil: sand: goat manure, soil: sand: husk charcoal, soil : sand: cocopeat. Data were analyzed by F test, if there were significant differences between treatments, then further tests were performed using a 5% LSD test. Observation variables included germination speed, percentage of germination, plant height, stem diameter, longest root length, root wet weight, root dry weight, number of leaves, plant wet weight, plant dry weight. The results showed that initial immersion temperature was significantly different in all variables, except for the number of leaves. The optimum initial immersion temperature is 60˚C (S2). The treatment of different types of planting media is very evident on all variables, except for the percentage of germination. The best type of planting media is soil: sand: goat manure (M1). There is an interaction between initial immersion temperature and type of planting media, namely the variable plant height, number of leaves, longest root length, root wet weight and plant wet weight. The best interaction is achieved by initial temperature of 60 ° C and type of soil planting media: sand: goat manure (S2M1).